2017
DOI: 10.3389/fneur.2017.00023
|View full text |Cite
|
Sign up to set email alerts
|

Inaccurate Saccades and Enhanced Vestibulo-Ocular Reflex Suppression during Combined Eye–Head Movements in Patients with Chronic Neck Pain: Possible Implications for Cervical Vertigo

Abstract: BackgroundThe primate ocular motor system is designed to acquire peripheral targets of interest by coordinating visual, vestibular, and neck muscle activation signals. The vestibulo-ocular reflex (VOR) is greatly reduced at the onset of large eye–head (gaze) saccades and resumes before the end of the saccades to stabilize eye-in-orbit and ensure accurate target acquisition. Previous studies have relied on manipulating head movements in normal individuals to study VOR suppression and gaze kinematics. We sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…Recent studies have identified possible objective measures of neck contribution in those diagnosed with cervical vertigo. 17,30,31 When compared to healthy control subjects, Johnston et al found that a prolonged reduction in vestibular response to head movement (ie, VOR) when patients attempted to acquire visual targets with cervical soft tissue disorders and normal neuro-otologic examinations. 31 Their results suggest that neck limitations, due to pain or stiffness, manifest an exaggerated proprioceptive response and subsequent disproportionate VOR suppression, which translates into subjective symptoms of dizziness and imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified possible objective measures of neck contribution in those diagnosed with cervical vertigo. 17,30,31 When compared to healthy control subjects, Johnston et al found that a prolonged reduction in vestibular response to head movement (ie, VOR) when patients attempted to acquire visual targets with cervical soft tissue disorders and normal neuro-otologic examinations. 31 Their results suggest that neck limitations, due to pain or stiffness, manifest an exaggerated proprioceptive response and subsequent disproportionate VOR suppression, which translates into subjective symptoms of dizziness and imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…In our population of patients with chronic soft-tissue rheumatic complaints, increased fall frequency and fear of falling occurred in patients who had reduced cervical mobility and increased mid-thoracic kyphoscoliosis. With chronic neck and upper back pain, horizontal head rotations become smaller, slower, longer, and more delayed over time, 11 as evidenced by negative correlations between head rotations and symptom duration in all faller cohorts. The consequence is head-on-trunk stability at the expense of gaze accuracy when making large unpredictable horizontal head-free gaze shifts.…”
Section: Discussionmentioning
confidence: 97%
“…10 Chronic cervical immobility prolongs VOR suppression during combined eye-head movements because coactivation of cervical muscles causes non-veridical sensory signals from neck proprioceptors. This in turn causes diminished gaze accuracy, 11 potentially impairing navigation through complex visual environments where it is essential to accurately redirect gaze to novel targets. We determined these abnormalities of saccade metrics and VOR suppression to be consistent and robust findings in patients with chronically restricted cervical mobility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature [31][32][33][34] showed how eye movement and nystagmus videos can be utilized in dizziness diagnosis. Theekapun Charoenpong et al [32] proposed a method to diagnose vertigo by measuring the eye movement velocity of nystagmus.…”
Section: Introductionmentioning
confidence: 99%